2000
DOI: 10.1530/eje.0.1420359
|View full text |Cite
|
Sign up to set email alerts
|

The GH response to low-dose bolus growth hormone-releasing hormone (GHRH(1-29)NH2) is attenuated in patients with longstanding post-irradiation GH insufficiency

Abstract: Objective: Previous studies have suggested that post-irradiation GH insufficiency results from a loss of GHRH secretion, since many patients were able to release GH following exogenous GHRH stimulation. However, supramaximal doses of GHRH were used and the response may decline with time after radiotherapy. We re-evaluated the GHRH dose-response curve in patients post cranial irradiation and in controls. Design: Randomized controlled study. Methods: Five adult male long-term survivors of childhood brain tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…The progressive nature of the hormonal deficits following radiation damage to the h-p axis can be attributed to secondary pituitary atrophy consequent upon lack of hypothalamic releasing/trophic factors [7,[21][22][23][24] or delayed direct effects of radiotherapy on the axis. The latter is supported by the gradual decline in the elevated prolactin levels seen in some patients after prolonged periods of follow up [20].…”
Section: Pathophysiology Of Radiation Damagementioning
confidence: 99%
See 2 more Smart Citations
“…The progressive nature of the hormonal deficits following radiation damage to the h-p axis can be attributed to secondary pituitary atrophy consequent upon lack of hypothalamic releasing/trophic factors [7,[21][22][23][24] or delayed direct effects of radiotherapy on the axis. The latter is supported by the gradual decline in the elevated prolactin levels seen in some patients after prolonged periods of follow up [20].…”
Section: Pathophysiology Of Radiation Damagementioning
confidence: 99%
“…Radiationinduced h-p axis dysfunction represents a pathology, in which discordant GH responses to mechanistically different provocative tests may be observed raising the question of which test reflects the true GH status. It has been suggested that radiation with doses less than 40 Gy causes predominant hypothalamic damage with GHRH deficiency; a hypothesis based on relative preservation or ''normality'' of responses to direct pituitary stimulation with exogenous GHRH compared with other provocative tests, especially the ITT [21,23,[37][38][39][40]. Therefore, the ITT has been considered to be the ''gold standard'' and frequently stated to be a more robust and sensitive test to identify radiationinduced GHD [41], such that a failed response to the ITT in cranially irradiated patients may be accepted as diagnostic of GHD without resort to further testing.…”
Section: Abnormalities Of Gh Secretion and Gh Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2). The progressive nature of the hormonal deficits following radiation damage to the h-p axis can be attributed to secondary pituitary atrophy consequent upon lack of hypothalamic releasing/trophic factors [7,16,[33][34][35] or delayed direct effects of radiotherapy on the axis. The latter is supported by the gradual decline in the elevated prolactin levels seen in some patients after prolonged periods of follow up [22].…”
Section: Pathophysiology and Site Of Radiation Damagementioning
confidence: 99%
“…Both increased incidence and severity of hormonal deficits are seen with longer post-irradiation follow-up intervals (Achermann et al, 2000;Clayton & Shalet, 1991;Lam et al, 1991;Littley et al, 1989b;Samaan et al, 1987;Schmiegelow et al, 2000) (Fig 1 &2). Secondary pituitary atrophy consequent upon lack of hypothalamic releasing/trophic factors accounts for the progressive nature of the hormonal deficits, in addition, to the delayed direct effects of radiotherapy on the axis.…”
Section: Introductionmentioning
confidence: 96%